Adding gender dimensions to bio-economic modelling: Insights from the literature - Fontana, Marzia (International Food Policy Research Institute, 2014)
Current international debates increasingly highlight the need to move countries towards more sustainable paths of development. These debates emphasise that there are three dimensions to sustainability: social, economic and environmental, which are deeply interconnected and need to be given equal policy attention. The linkages be-tween social, environmental and economic dimensions are complex. They involve synergies but also trade-offs, such as the tensions that may arise between prioritizing food or biofuel in land use, to name just one example. How such tensions are addressed has important consequences for the way in which gains and losses are distrib-uted across social groups.